2017
DOI: 10.1177/0300060517708942
|View full text |Cite
|
Sign up to set email alerts
|

Early vitrectomy for dense vitreous hemorrhage in adults with non-traumatic and non-diabetic retinopathy

Abstract: ObjectiveTo evaluate the etiologies for dense vitreous hemorrhage in adults with non-traumatic and reveal management of early vitrectomy for the disease.MethodsStudy included 105 eyes from 105 patients. Outcome measures were etiologies of vitreous hemorrhage, formation of retinal and/or disk neovascular membrane (NVM), incidence of retinal tear and detachment, visual acuity (VA) and postoperative complications.ResultsMean time between presentation and surgery was 7.1 days. The most common etiologies were retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
2
12
1
Order By: Relevance
“…3,5,8 In this study, PDR was the most common cause of vitreous hemorrhage (49.4%). This finding differs with Zhang et al 9 that reported age macular degeneration (AMD) was the most common cause.…”
Section: Resultscontrasting
confidence: 94%
“…3,5,8 In this study, PDR was the most common cause of vitreous hemorrhage (49.4%). This finding differs with Zhang et al 9 that reported age macular degeneration (AMD) was the most common cause.…”
Section: Resultscontrasting
confidence: 94%
“…Vitrectomy combined with laser photocoagulation and with or without tamponade agents according to the etiology is the recommended treatment for vitreous hemorrhage. 6 The causes of poor visual outcome less than 6/60 were chorioretinal scar in four eyes, optic atrophy in one eye and epiretinal membrane formation in one eye. The complications of vitrectomy were seen in 8 (17.4%) eyes.…”
Section: Discussionmentioning
confidence: 93%
“…The severity of vitreous hemorrhage was graded on a 5-point scale from a previous study: Grade 0 (no vitreous hemorrhage); Grade 1 (minimal vitreous hemorrhage, optic disk, and retinal vessels were clearly visible); Grade 2 (mild vitreous hemorrhage, most of the optic disk, and retinal vessels were visible); Grade 3 (moderate vitreous hemorrhage, optic disk, or retinal vessels were barely visible); and Grade 4 (severe vitreous hemorrhage was too dense to allow visualization of the optic disk). 6 Early vitrectomy was defined as the time between decision for surgery and actual surgery if done within 7 days. We included cases with early vitrectomy for vitreous hemorrhage of Grade 3 or 4 that had a follow-up of at least 3 months.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…In cases of VH in the setting of PDR, the haemorrhage may clear over time with conservative measures, and prognosis is generally good for regaining baseline VA. However, vitrectomy is recommended for patients who have VH refractory to conservative therapy, significant haemorrhage, or co‐morbidities like retinal tears or significant tractional membranes 92 . Furthermore, the Diabetic Retinopathy Vitrectomy Study demonstrated that type 1 diabetics with poor VA due to a non‐clearing VH should undergo early vitrectomy (ie, within 6 months) 93 .…”
Section: Current Recommendations For Diabetic Eye Disease Managementmentioning
confidence: 99%
“…However, vitrectomy is recommended for patients who have VH refractory to conservative therapy, significant haemorrhage, or co-morbidities like retinal tears or significant tractional membranes. 92 Furthermore, the Diabetic Retinopathy Vitrectomy Study demonstrated that type 1 diabetics with poor VA due to a non-clearing VH should undergo early vitrectomy (ie, within 6 months). 93 Early vitrectomy should also be considered in any diabetic patient with anterior hyaloidal fibrovascular proliferation, refractory macular oedema, progressive proliferative retinopathy despite PRP, and/or ghost cell glaucoma from long-standing VH.…”
Section: Proliferative Diabetic Retinopathymentioning
confidence: 99%